2015
DOI: 10.1039/c5ra09228k
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of quinoline from liquid hydrocarbons on graphite oxide and activated carbons

Abstract: Four carbon-based adsorbents (activated carbon, oxidatively modified activated carbon, graphite, and graphite oxide) were investigated as adsorbents for selective removing quinoline from a model hydrocarbon fuel. The surface chemical properties of these carbon-based adsorbents were characterized by temperatureprogrammed desorption coupled with mass spectrometry (TPD-MS), X-ray photoelectron spectroscopy (XRD), elementary analysis (EA) and nitrogen adsorption-desorption analyzer in detail. The influences of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 53 publications
(156 reference statements)
0
11
0
Order By: Relevance
“…The CO evolved can be observed at the temperature range of 90 to 160 °C. CO gas detected at this temperature range is due to thermal decomposition of basal plane oxygen groups such as epoxides and alcohols 52,53 . The integrated area for CO evolving from 3xGO (7.76 × 10 −8 Torr) is greater than that of 2xGO (5.06 × 10 −8 Torr), indicating the relatively higher quantity of epoxide and alcohol groups on the surface of 3xGO.…”
Section: Resultsmentioning
confidence: 95%
“…The CO evolved can be observed at the temperature range of 90 to 160 °C. CO gas detected at this temperature range is due to thermal decomposition of basal plane oxygen groups such as epoxides and alcohols 52,53 . The integrated area for CO evolving from 3xGO (7.76 × 10 −8 Torr) is greater than that of 2xGO (5.06 × 10 −8 Torr), indicating the relatively higher quantity of epoxide and alcohol groups on the surface of 3xGO.…”
Section: Resultsmentioning
confidence: 95%
“…Hydrodenitrogenation (HDN) and hydrodesulfurization (HDS) are the common methods used worldwide in oil refineries for the removal of nitrogen compounds in light and medium crude oil products, such as naphtha, kerosene, and diesel, in hydrotreatment (HDT) units. Nevertheless, a typical HDT process requires elevated temperature, high pressure, and high hydrogen consumption. , Other approaches could also be proposed, for example, adsorptive denitrogenation, , oxidative denitrogenation, and extractive denitrogenation. , However, all of these are usually used on a bench scale. The advantage of using an adsorption process for the removal of sulfur and nitrogen compounds in hydrocarbons is that these processes would not have intensive energy consumption, such as a HDT process, where high pressures and temperatures of operation are required.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of using an adsorption process for the removal of sulfur and nitrogen compounds in hydrocarbons is that these processes would not have intensive energy consumption, such as a HDT process, where high pressures and temperatures of operation are required. An adsorption process would not generate a large amount of byproducts, as in an oxidative process, and could be performed with a wide range of adsorbents, such as metal oxides, silica gel, zeolites, ion-exchange resins, activated alumina, activated carbon, polymeric adsorbents, graphite, and graphite oxide. ,, Adsorption material selection depends upon the type of chemical compound that will be removed, taking into consideration its adsorption capacity, selectivity, regenerability, lifetime, and price of the adsorbent . In 2015, Feng et al suggested the use of four carbon-based adsorbents (activated carbon, oxidatively modified activated carbon, graphite, and graphite oxide) to selectively remove quinoline from a model hydrocarbon fuel.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations